Structural and mechanical characterization of detonation coatings formed by reaction products of titanium with components of the spraying atmosphere - Ulianitsk V. Yu.; Batraev I. S.; Dudina D. V.; Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Bokhonov B. B. (Научные основы разработки материалов с многоуровневой иерархической структурой, в том числе для экстремальных условий эксплуатации, 2016)
Заглавие с экрана